Prevalence and Complications of Metabolic Syndrome among Rheumatoid Arthritis Patients in Aswan - Sayed , Aml Ahmed; Abdallah , Omar Abdelrahman Ahmed; Sayed, Zain Elabdeen Ahmed; Abdelhameid, Marwa Ahmed (Journal of Ecohumanism, 2024)
Objectivity: Rheumatoid Arthritis (RA) is the most common inflammatory rheumatic disease. Prevalence of metabolic syndrome (MetS) varies widely in the literature. We conducted this study to detect the prevalence and complications of metabolic syndrome among RA patients and its association to disease activity and chronicity. Methods: This Cross-sectional study was conducted between January 2023 and December 2023, included 200 patients who were diagnosed as RA. Data collected from the eligible patients included full medical history and investigations included complete blood count, lipid profile, fasting blood glucose (FBG), uric acid, urea, creatinine, Alanine Aminotransferase, Aspartate aminotransferase, alkaline phosphates, electrocardiography and echocardiography. Patients were allocated to four groups (50 for each group) based on RA disease activity and duration. Group 1: acute active RA patients, Group 2: acute inactive RA patients, Group 3: chronic active RA patients and Group 4: chronic inactive RA patients. Results: The present study was conducted on 200 patients with RA; the majority of them were females (152). The patient’s mean age was 47±11 years, the mean± SD of their waist circumference was 101.6± 13.96. MetS prevalence in RA patients was 52% (104 patients), with a higher occurrence in chronic RA cases (30%) compared to acute RA (22%). Our study demonstrates a significant difference in MetS prevalence among the four groups. Conclusions: MetS prevalence among RA patients is associated with disease activity and duration. Hyperuricemia, increased liver enzymes and renal chemistry are the most prevalent factors linked to MetS in RA.